Food Safety Handbook : A Practical Guide for Building a Robust Food Safety Management System - International Finance Corporation (Washington, DC: World Bank, 2020)
The Food Safety Handbook: A Practical Guide for Building a Robust Food Safety Management System, contains detailed information on food safety systems and what large and small food industry companies can do to establish, maintain, and enhance food safety in their operations. This new edition updates the guidelines and regulations since the previous 2016 edition, drawing on best practices and the knowledge IFC has gained in supporting food business operators around the world. The Food Safety Handbook is indispensable for all food business operators -- anywhere along the food production and processing value chain -- who want to develop a new food safety system or strengthen an existing one.